Strengthening Students’ Characters and Ecopreneurship through Science, Environment, Technology, and Society Course (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
The purpose of this research was to strengthen characters and ecopreneurship of students who enrolled in science, environment, technology, and society (SETS) course. The focus of the students’ characters in this study included responsibility, discipline, creative and innovative, commitment, and cooperative. This course supports the students to develop ecopreneurship to create products from organic and inorganic waste treatments. To achieve the purpose of this research, a teaching and learning package including syllabus, lesson plan, and assessment criteria were developed using the Research and Development (RD) method. A total of 42 science education undergraduates and two experts were involved in this research. The data were collected through validation sheets, observation sheets, and assessment of students’ecopreneurship products. The validation results showed that the developed teaching and learning package categorized as very good. In this course, six stages of learning were implemented including identifying a problem, making a plan, conducting an observation, collecting information, exhibiting a product, and writing ideas. The observation results showed that the overall developed teaching and learning package was effective to support the students’ learning in each of the six stages. Moreover, the improvement in students’ scores on the focused characters was observed. At the end of the course, the students’ ecopreneurship products were also accomplished. Nine of the products were made of organic waste, while the two of them were recycled from inorganic waste. Thus, it concluded that the course of science, environment, technology, and society could strengthen the students’ characters and ecopreneurship.